Pendidikan Buddhis Di Era Milenial - Andi Budiman; Bima Dian (Jurnal Budi Pekerti Agama Buddha, 2023)
Communication in Buddhist community groups in Wonogiri Regency is basically inseparable from communication aspects consisting of communicators, messages, audiences or communicants and the effects that arise afterwards communication occurs. In Buddhist community groups in Wonogiri Regency, communication between group members and religious leaders, as well as between group members, occurs not only at certain times or activities but takes place at any time and at any time, because group members are part of a community that always interacts. Relationships (relationships) and communication that are closely intertwined among members of the Buddhist community group in Wonogiri Regency make the community a strong (strong) group. Cohesiveness (cohesiveness) is a factor that can lead to the emergence of groupthink. This integration brings certain consequences, in group decision making. Decision making is a systematic approach to the nature of a problem by collecting facts and data and determining mature alternatives to take an appropriate action (Siregar, 2013: 2) and also determining mature alternatives to take an appropriate action.